Soil water isotopes from West Africa (Benin and Senegal) - Alexandre, Anne (In: Alexandre, A (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133, 2025)
Isotopic composition of soil water extracted by centrifugation and analyzed by Cavity Ring Dow Spectroscopy (CRDS) from 10 soil cores collected at Belefoungou (BE, Benin), Nalohou (NA, Benin) and Dahra (DA, Senegal). For comparison, the isotopic composition of precipitation preceding the samplings are shown.
Keywords: phytolith; plant water; precipitation; soil water; triple oxygen isotopes; West Africa